MAFLD in Egyptian non-dialysis CKD Patients: Frequency, fibrosis severity, and risk factors - Zienab M. Saad; Hesham K. H. Keryakos; Hala A. Hassanin; Mahmoud M. Higazi; Manar M. Sayed; Doaa E. Ismail; Safaa M. Abdelhalim (PLoS ONE, 2025)
Introduction The prevalence of Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) in non-dialysis chronic kidney disease (CKD) patients remains underexplored, particularly in high-risk populations such as Egyptians with high rates of metabolic disorders. Aims This study aimed to determine the frequency of MAFLD in Egyptian non-dialysis CKD patients, assess liver fibrosis severity, and identify associated metabolic risk factors. Methods A cross-sectional study of 108 CKD patients was conducted, with participants stratified into MAFLD (n = 64) and non-MAFLD (n = 44) groups. Diagnostic criteria for MAFLD included hepatic steatosis (ultrasonography) and metabolic risk factors. Non-invasive fibrosis scores (NAFLD score, FIB-4 index, APRI score) and shear wave elastography were used to evaluate liver fibrosis. Results MAFLD prevalence was 59.25%. MAFLD patients exhibited significant associations with older age (56 ± 17.1 vs. 43 ± 17.1 years, p < 0.001 ), higher BMI (34.5 ± 6.2 vs. 27.2 ± 5.7 kg/m 2 , p < 0.001 ), diabetes (48.4% vs. 4.5%, p < 0.001 ), hypertension (68.7% vs. 22.7%, p < 0.001 ), and insulin resistance (HOMA-IR: 3.5 ± 3.6 vs. 1.45 ± 1.03, p < 0.001 ). MAFLD patients also had lower eGFR (40.5 ± 28.0 vs. 58.9 ± 39.9 mL/min/1.73 m 2 , p = 0.017 ) and higher liver stiffness (7.6 ± 1.8 vs. 6.9 ± 1.7 kPa, p = 0.047 ), with advanced fibrosis more prevalent in later CKD stages.. Conclusion MAFLD is highly prevalent among non-dialysis CKD patients, driven by shared metabolic abnormalities and CKD severity. These findings highlight the bidirectional relationship between MAFLD and CKD, emphasizing the need for integrated screening and management strategies to mitigate progression risks in this population.